2020
DOI: 10.31434/rms.v5i3.391
|View full text |Cite
|
Sign up to set email alerts
|

Delirium en el adulto mayor

Abstract: El delirium en el adulto mayor es una complicación común observada en pacientes adultos mayores. Se puede clasificar en tres tipos según el nivel de estado de alerta y actividad física del paciente, estos son hiperactivo, hipoactivo y mixto. Todos los pacientes manifiestan principalmente una alteración del estado de conciencia y falta de atención. Para diagnosticarla se utilizan los criterios diagnósticos del manual diagnóstico y estadístico de los trastornos mentales en su quinta edición. El manejo inicial se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…It was evidenced in the results that maintaining electrolytes, pH, bicarbonate, and hematocrits are necessary variables to measure during the patient’s clinical signs and symptoms. This agrees with that explained by Artola et al, ( 25 who reported that early detection of dehydration signs, states of oliguria added to maintaining a hydric balance lead to early identification of hydro-electrolyte alterations and, with this, permit unifying correct treatment actions by the interdisciplinary team.…”
Section: Discussionsupporting
confidence: 92%
“…It was evidenced in the results that maintaining electrolytes, pH, bicarbonate, and hematocrits are necessary variables to measure during the patient’s clinical signs and symptoms. This agrees with that explained by Artola et al, ( 25 who reported that early detection of dehydration signs, states of oliguria added to maintaining a hydric balance lead to early identification of hydro-electrolyte alterations and, with this, permit unifying correct treatment actions by the interdisciplinary team.…”
Section: Discussionsupporting
confidence: 92%
“…If the physician has the result of the 4AT scale screening when the physician performs the assessment, he has more information and could perform a faster assessment and therefore prescribe a treatment in less time, which would mean that the nursing professional could administer the treatment earlier. The literature states that early detection enables prompt diagnosis and treatment, and this is associated with shorter and less severe episodes of delirium ( 34 ). The mean length of hospital stay following the ED episode was shorter in participants screened with the 4AT scale than in patients who did not undergo screening (6.9 SD 8.9 days vs. 13.3 SD 44.0 days).…”
Section: Discussionmentioning
confidence: 99%
“…Esta reducción puede incrementar la probabilidad de desarrollar enfermedades y complicaciones (Cárdenas et al, 2021;Kalra & Sharma, 2018). Entre ellas se encuentra el delirio, el cual es la complicación más común presente en mayores de 65 años (Blanco et al, 2020). De igual manera, la diabetes representa una proporción significativa dentro de este grupo (Kalra & Sharma, 2018).…”
Section: Persona Mayorunclassified